Mathematical Modelling of the Transmission of Malaria. - Atubangire, Felix (Kabale University, 2024)
In this report, we present a mathematical model for the transmission of malaria by female anopheles mosquitos. We determine the invariant region in which our model system lies. We clearly show the mechanism by which malaria spreads from one person to another. The model takes in the ordinally differential equations. The basic reproduction number Ro is obtained. A stability analysis of the disease-free equilibrium was carried out for the case where there is no malaria in the population. Sensitivity analysis of the parameters to basic reproduction number. The results show that the basic reproduction number Ro is more sensitive to natural mortality. All working steps are included.